The Effect of Initial Groundwater Table and Rainfall Wetting Towards Slope Stability (Case Study of Landslide in Tangkil Hamlet, Banaran Village, Pulung Subdistrict, Ponorogo Regency) - Diana Ariesta (Journal of the Civil Engineering Forum, 2019)
Landslide is a natural phenomenon that can be controlled by a combination of various factors, such as topography, lithological condition, geological structure, water table, etc. Landslide is stated as a natural disaster if it causes casualties, direct losses and subsequent impacts of the initial destruction, as happened in Banaran Village, Ponorogo Regency. This study is aimed to examine the effects of initial groundwater table conditions and rainfall wetting on Banaran Village landslide. This study was conducted by assuming scenarios of initial groundwater table conditions. Soil parameters were obtained by testing soil samples in the laboratory. Infiltration parameters were acquired through permeability tests using the Philip-Dunne method, while areal rainfall was calculated using the Thiessen polygon method. In addition, slope stability modeling was calculated by using SLOPE/W while rainfall wetting analysis was carried out through SEEP/W. The analysis of Banaran Village landslide through these two numerical models was conducted by considering two conditions: 1) without rainfall and 2) with rainfall and infiltration. The analysis results imply that the landslide occurred in the initial groundwater table condition in scenario 3 with a safety factor of 1.008, and in a similar scenario with a safety factor of 0.973 when taking into account rainfall and infiltration. The results from SEEP/W and SLOPE/W indicate that the initial condition of the groundwater table highly influenced the decrease of the safety factor, while the wetting process did not cause a significant decrease of the safety factor.